لمحات من جهود المحدِّثين في التربية والتعليم: قراءة في ضوء مباحث الإدارة التربوية: The Muhaddithin’s Practices in Teaching and Education: A Reading from the Perspective of Educational Administration - Bin Jamil, Khairil Husaini; Jamil, Asyraf Isyraqi (Journal of Islamic Educational Research, 2019)
History has reported the great achievements of Muslim scholars in various fields of knowledge and art, and their efforts towards the development of knowledge and future generation’s education. Amongst the profound heritage of those luminaries include the contribution of prominent scholars of al-sunnah and the traditions of prophet Muhammad. They have not only disseminated the hadiths of Prophet Muhammad to the Muslim community, but also educate their students and followers. Following this argument, this research will highlight the efforts of the muhaddithin in the field of education and teaching, as well as their contributions in various aspects of educational management. For example, this research will present the muhaddithin’s practices in subjects such as journeying to seek knowledge, educational representative, al-sama’ (auditory) sessions and its attendance record, selection of shuyukh (teachers), rearing talamiz (students), providing ijazah (certification) and verifying the riwayah (the reporter’s credibility), evaluating qualifications, syllabus writing, the management of dar al-hadith (special institute for learning hadith), recreational activities, interaction amongst muhaddithin, social responsibility, etc. This paper will analyse these various practices from the perspective of modern educational administration, teaching management or school management, and hope to facilitate the appreciation of the muhaddithin’s tradition in the educational endeavours.